2011
DOI: 10.1007/s13146-011-0054-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and oxygen isotopic variations in stromatolitic dolomites of Palaeoproterozoic Vempalle Formation, Cuddapah Basin, India

Abstract: The marine stromatolitic dolomites of Palaeoproterozoic Vempalle Formation, of Cuddapah Basin, South India show significantly depleted d 18 O (-8.19 to -18.25%) and d 13 C (-0.03 to -5.74) values and are consistent with the global Proterozoic data. A comparison of the stable isotope values from major localities of Proterozoic Basins of India has also been attempted in this study. Significantly depleted d 18 O values of Vempalle carbonate samples could not be considered to be postdepositional modifications as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 49 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…). On the other hand,Chakrabarti et al (2011Chakrabarti et al ( , 2014, using isotopic ( 13 C and  18 O) and elemental (Mg, Ca, Fe, Mn, Sr and SO 4 -2 ) data, concluded that VF dolomite is primary in nature and precipitated either from 18 O depleted marine water or from a geochemically distinct mixed fluid source. Based on collective geochemical signatures,  13 C and  18 O isotopic values, flat REE patterns along with Ce, Eu and Gd anomalies, and chondritic to superchondritic Y/Ho ratios, have recently…”
mentioning
confidence: 99%
“…). On the other hand,Chakrabarti et al (2011Chakrabarti et al ( , 2014, using isotopic ( 13 C and  18 O) and elemental (Mg, Ca, Fe, Mn, Sr and SO 4 -2 ) data, concluded that VF dolomite is primary in nature and precipitated either from 18 O depleted marine water or from a geochemically distinct mixed fluid source. Based on collective geochemical signatures,  13 C and  18 O isotopic values, flat REE patterns along with Ce, Eu and Gd anomalies, and chondritic to superchondritic Y/Ho ratios, have recently…”
mentioning
confidence: 99%